Hyperspectral coherent Raman imaging – principle, theory, instrumentation, and applications to life sciences. (8th December 2015) - Kano, Hideaki; Segawa, Hiroki; Okuno, Masanari; Leproux, Philippe; Couderc, Vincent
Abstract : Coherent Raman scattering microscopy such as coherent anti‐Stokes Raman scattering and stimulated Raman scattering microscopy boosts the weak Raman signal and enables us to perform label‐free visualization of the molecular distribution and its dynamical behavior in living cells and tissues with high speed. In comparison with fluorescence imaging, cells and tissues can be visualized without specifying the target molecule. In this review, we describe the characteristics of a hyperspectral coherent Raman imaging method, which is capable of acquiring both spectra and images simultaneously, and review applications to life sciences. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Coherent anti‐Stokes Raman scattering spectroscopic imaging of L929 cells. Im[χ (3) ] spectra obtained by maximum entropy method after singular value decomposition denoising (a); hyperspectral coherent anti‐Stokes Raman scattering image at each vibrational mode (b–d); and merged result (e).